2014
DOI: 10.1002/2014je004636
|View full text |Cite
|
Sign up to set email alerts
|

Coronae formation on Venus via extension and lithospheric instability

Abstract: Over 500 quasi-circular volcano-tectonic features called coronae occur on Venus. They are believed to form via small-scale mantle upwellings, lithospheric instability, or a combination thereof. Coronae and rifts commonly occur together, including many coronae that lie outside of the fracture zone. However, the genetic link between the two has remained unclear. This paper proposes a mechanism for the formation of off-rift coronae due to the rifting process. We model the interaction of a rising mantle plume asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 56 publications
0
16
0
Order By: Relevance
“…However, models with lithosphere downwelling into the mantle like Rayleigh‐Taylor instabilities may also account for the topographic morphology (e.g., Grindrod & Hoogenboom, ; Hoogenboom & Houseman, ; Tackley & Stevenson, ). Hybrid processes involving the interaction between a mantle plume and an adjacent, downwelling instability may have formed the coronae associated with large rifts (Piskorz et al, ). Plume‐induced rollback subduction predicts many of the deformation structures seen at larger coronae, such as deep, narrow trenches surrounding only part of the corona circumference (Davaille et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…However, models with lithosphere downwelling into the mantle like Rayleigh‐Taylor instabilities may also account for the topographic morphology (e.g., Grindrod & Hoogenboom, ; Hoogenboom & Houseman, ; Tackley & Stevenson, ). Hybrid processes involving the interaction between a mantle plume and an adjacent, downwelling instability may have formed the coronae associated with large rifts (Piskorz et al, ). Plume‐induced rollback subduction predicts many of the deformation structures seen at larger coronae, such as deep, narrow trenches surrounding only part of the corona circumference (Davaille et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Their wide variety of topographic shapes, including depressions, domes, and plateaus, often surrounded by troughs and rises ) allows for possible origins as small scale mantle upwellings, delamination or subduction, a combination of upwelling and downwelling, and deformation or construction due to magmatic processes ( McKenzie et al, 1992;Sandwell and Schubert, 1992;Squyres et al, 1992;Schubert and Sandwell, 1995;Koch and Manga, 1996;Hoogenboom and Houseman, 2006;Dombard et al, 2007;Gerya, 2014;Piskorz et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Stofan et al [2001b] break down the corona population into two subdivisions: type 1 coronae with >50% fracture annuli and the much more poorly defined type 2 coronae with <50% fracture annuli, the former occurring predominantly on rifts and fracture belts and the latter occurring predominantly on the plains. Models of coronae formation include the delamination and deformation of the lithosphere via magma upwelling [Smrekar and Stofan, 1997], the deformational response of the lithosphere when loaded via magmatic intrusion [Dombard et al, 2007], upwelling-induced crustal convection [Gerya, 2014], and ring-like dripping via Rayleigh-Taylor instabilities of a dense layer at the base of the lithosphere at plume margins [Piskorz et al, 2014]. Arachnoids are thought to be formed by uplift and relaxation by magmatic diapirs formed over mantle plumes [Aittola and Kostama, 2000;Krassilnikov, 2002].…”
Section: Journal Of Geophysical Research: Planetsmentioning
confidence: 99%
“…Martin et al [], however, found their distribution to be indistinguishable from random within 1500 km of Parga Chasma. An apparent genetic link between coronae and rift systems is well documented [ Solomon et al , ; Baer et al , ; Smrekar and Stofan , ; Martin et al , ; Piskorz et al , ] but has yet to be adequately explained. Arachnoids on the other hand have previously been noted to tend to cluster on the plains, in contrast to novae, which tend to follow sparse chains [ Aittola and Kostama , ].…”
Section: Introductionmentioning
confidence: 99%